The effect of collaboration, visibility, velocity, and flexibility on supply chain resilience: A case study on Pacific Roadlink Logistics, Inc. - Go, Brandon Patrick Chong (Animo Repository, 2022)
The trucking industry is a vital pillar of all economies, especially the Philippine economy. With the rise of the economy also comes the rise of logistics and transport industry. As production and distribution of goods increase, so does the need to move these items. This paper aims to assess the effect of collaboration, visibility, velocity, and flexibility on the supply chain resilience of Pacific Roadlink Logistics, Inc. (PRLI). A total of 66 respondents constitutes the sample of the study, consisting of middle management employees across all depots nationwide. Eight research questions and eight hypotheses were generated and tested at 5% (0.05) significance level using descriptive statistics and path analysis to quantify the relationships among multiple variables (Wright, 1918, 1921). Data were then analyzed through Partial Least Squares - Structural Equation Modeling (PLS-SEM) using the WarpPLS 7.0 software. Results showed that all independent variables: collaboration, visibility, velocity, and flexibility have a positive relationship with PRLI’s supply chain resilience. Furthermore, results also show that collaboration, visibility, and flexibility have a significant impact on PRLI’s supply chain resilience. However, results showed that velocity did not have a significant impact on PRLI’s supply chain resilience. The research concludes that the supply chain capabilities play a crucial role in the supply chain resilience of PRLI and its supply chain partners. The key recommendations of the paper help enhance these capabilities to improve the resilience of its supply chain. These key recommendations include fostering intrapreneurship culture, GPS real-time tracking, satellite phone issuance, and third party logistics partners.